(untitled) - NOVITA PERMATA SARI, AISYAH (RETAIN : Journal of Research in English Language Teaching, 2014)
ABSTRAK According to observation in MTsN Mojosari, it has been found that were there are some problems in classroom. There are many students cannot speak well. Because the students seldom practiceing English speaking. They felt afraid to make some errors in speaking English It made the students prefer to be quite or passive in class. To overcome this problem, this study was designed to solve the problem using media snakes and ladders games, and investigate the use of snakes and ladders games in speaking class in improving students speaking ability. This Study was an experimental quantitative study which had the students of VII A as experimental group and VII B as control group of MTsNMojosari, Mojokerto, as the participants. It was found that there was increasing mean of experimental group. The increasing mean of experimental group prove that the treatment by using snakes and ladders game could improve the students’ speaking ability in speaking class. From the calculation of t-test, it was showed the result of t-value was 8.88, which is higher than t-table (1.98). It showed that there was a significant improvement after conduction of treatment. Thus snakes and ladders game was an effective media to improve students’ speaking skills. Therefore the advantages of snakes and ladders game were proven. It could encourage students’ speaking confidence, develop students’ speaking fluency, and group development related to the a short conversation about asking and giving service. The researcher used at least three categories of students’ responses in the questionnaire, including interested, motivated, and helped. Based on the tables and charts, most students respond that snakes and ladders game was an effective media for learning asking and giving service in speaking. They were interesting, motivating, and helpful in order to learn the asking and giving service activier in speaking by using snakes and ladders game. Key words: Snakes and ladders game, Media, and the Improvement Speaking ABSTRAK Menurut observasi di MTsN Mojosari, telah ditemukan beberapa masalah di dalam kelas. Ada banyak siswa tidak dapat berbicara dengan baik.Karena mereka jarang mempraktekan berbicara bahasa inggris.Mereka merasa takut untuk membuat kesalahan dalam berbicara inggris. Hal ini membuat siswa lebih suka untuk diam dan pasif di dalam kelas.Untuk mengatasi masalah ini, penelitian ini dibentuk untuk memecahkan masalah menggunakan media ular tangga, dan menyelidiki penggunaan dari permainan ular tangga dalam kelas berbicara dalam meningkatkan kemampuan berbicara siswa. penelitian ini merupakan sebuah penelitian eksperimental quantitative, oartisipan dalam penelitian ini mencakup para siswa kelas VII A sebagai kelas Ekperimental dan VII B sebagai kelas control dari MTsN Mojosari kota Mojokerto. Dalam penelitian ini diketahui bahwa ada kenaikan rata-rata dari grup eksperimental. Kenaikan nilai rata-rata dari grup experimental membuktikan bahwa penggunaan permainan ular tangga dapat meningkatkan kemampuan berbicara siswa dalam kelas.Dari perhitungan t-test, menunjukkan hasil dari t-value adalah 8.88 yang lebih tinggi dari pada t- tabel yaitu 1.98. Itu dapat terlihat bahwa ada peningkatan yang significant setelah dilakukan treatment.Demikian permainan ular tangga merupakan media yang efektif untuk meningkatkan keahlian berbicara siswa . Oleh karena itu keuntungan dari permainan ular tangga telah terbukti. Ini dapat mendorong siswa yakin untuk berbicara,mengembangkan kelancaran berbicara siswa, dan perkembangan grup dalam percakapan pendek tentang meminta dan memberi jasa. Peneliti menggunakan kurang lebih tiga kategori dari respon siswa dalam angket, yang meliputi,ketertarikan, dapat dimengerti, dan berpengaruh. Dari tabel dan grafik, lebih banyak siswa merespon bahwa permainan ular tangga merupakan media yang effektik untuk pembelajaran menerima dan meminta jasa dalam berbicara. Mereka tertarik, termotivasi dan terbantu untuk belajar meminta dan memberi jasa secara aktif dalam berbicara dengan menggunakan permainan ular tangga. KataKunci:Permainanulartangga,media,danPeingkatanberbicara.